(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the awareness, acceptance and the reasons of refusal of PPIUCD in antenatal women. Study Design: Cross sectional study Place & duration of study: The study was conducted in Gynae unit 1 Sir Ganga Ram Hospital Lahore for the period of 1 year (Jan 2015 to Dec 2015). Methodology: After approval from the ethical committee of the Sir Ganga Ram Hospital Lahore, 505 eligible pregnant women attending the OPD and labour room were enrolled in the study. Informed consent was taken. Non-probability convenience sampling technique was used. Afterwards they were counseled for PPIUCD and a validated questionnaire including age, parity, educational and socioeconomic status, awareness of PPIUCD, willingness for PPIUCD insertion and reasons of refusal was used to collect data. Logistic regression analysis was used to find out significance of the above-mentioned factors. Results: The mean age of women was 27.7 years ±SD 4.4. Only 22.38% females were aware of PPIUCD. Acceptance rate of PPIUCD was 53.27% and 38.42% women refused PPIUCD, while 8.32% women were convinced but wanted to discuss with family. The most frequent reason of rejection identified was husband and family disagreement (28.9%) followed by desire of permanent contraceptive method, requirement of short-term contraception, fear of side effects, satisfaction with previous method, myths and religious beliefs. Acceptance rate was highest (58.5%) amongst P2-4. Acceptance rate was higher (71%) in women who were already aware of PPIUCD. Conclusion: The awareness about availability of PPIUCD is quite low because it is recently introduced in the family planning methods. The acceptance rate of PPIUCD after dedicated counseling is good despite low awareness. The most frequent reason of refusal is husband and family disagreement. The acceptance can further be enhanced by dissemination of information and appropriate counseling in antenatal clinic.